Diagnostic patterns of haemoglobinopathies: A prospective observational study using high-performance liquid chromatography in a remote tertiary care center of Telangana. - Dr. Sumayya; Dr . Charitha Sravanthi Battu; Dr . K Raja Kumar (Student's Journal of Health Research Africa)
Background Haemoglobinopathies, including sickle cell disorders and thalassemias, are significant genetic conditions that alter hemoglobin structure and function. High-performance liquid chromatography is a sensitive and reliable tool for identifying hemoglobin variants. This study aimed to analyze the diagnostic patterns of haemoglobinopathies using HPLC in a tertiary care center serving the tribal population of Telangana.